Prevention, control, and elimination of neglected diseases in the Americas: Pathways to integrated, inter-programmatic, inter-sectoral action for health and development - Genovese Miguel A; Ippolito-Shepherd Josefa; Cerqueira Maria; Vasquez Javier; Rojas Rocio; Ault Steven K; Ehrenberg John P; Holveck John C; Periago Mirta (BMC, 2007)
Abstract Background In the Latin America and Caribbean region over 210 million people live below the poverty line. These impoverished and marginalized populations are heavily burdened with neglected communicable diseases. These diseases continue to enact a toll, not only on families and communities, but on the economically constrained countries themselves. Discussion As national public health priorities, neglected communicable diseases typically maintain a low profile and are often left out when public health agendas are formulated. While many of the neglected diseases do not directly cause high rates of mortality, they contribute to an enormous rate of morbidity and a drastic reduction in income for the most poverty-stricken families and communities. The persistence of this "vicious cycle" between poverty and poor health demonstrates the importance of linking the activities of the health sector with those of other sectors such as education, housing, water and sanitation, labor, public works, transportation, agriculture, industry, and economic development. Summary The purpose of this paper is three fold. First, it focuses on a need for integrated "pro-poor" approaches and policies to be developed in order to more adequately address the multi-faceted nature of neglected diseases. This represents a move away from traditional disease-centered approaches to a holistic approach that looks at the overarching causes and mechanisms that influence the health and well being of communities. The second objective of the paper outlines the need for a specific strategy for addressing these diseases and offers several programmatic entry points in the context of broad public health measures involving multiple sectors. Finally, the paper presents several current Pan American Health Organization and other institutional initiatives that already document the importance of integrated, inter-programmatic, and inter-sectoral approaches. They provide the framework for a renewed effort toward the efficient use of resources and the development of a comprehensive integrated solution to neglected communicable diseases found in the context of poverty, and tailored to the needs of local communities.